2017
DOI: 10.1038/s41598-017-15625-w
|View full text |Cite
|
Sign up to set email alerts
|

A high-density consensus linkage map of white lupin highlights synteny with narrow-leafed lupin and provides markers tagging key agronomic traits

Abstract: White lupin (Lupinus albus L.) is a valuable source of seed protein, carbohydrates and oil, but requires genetic improvement to attain its agronomic potential. This study aimed to (i) develop a new high-density consensus linkage map based on new, transcriptome-anchored markers; (ii) map four important agronomic traits, namely, vernalization requirement, seed alkaloid content, and resistance to anthracnose and Phomopsis stem blight; and, (iii) define regions of synteny between the L. albus and narrow-leafed lup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
90
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 88 publications
1
90
2
Order By: Relevance
“…The production of 94 Gb of very long reads along with a depth of 208× (119 Gb) of Illumina 150 bp paired-end sequences for the assembly polishing and with the addition of Bionano optical map technology allowed a genome assembly of 451 Mb. The contig sequences obtained by a meta assembly strategy based on CANU 15 and FALCON 16 were scaffolded in a first step using a Bionano optical map and in a second step using a high density genetic map 17 . The chromosome-level assembly (termed Lalb, Table 1, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of 94 Gb of very long reads along with a depth of 208× (119 Gb) of Illumina 150 bp paired-end sequences for the assembly polishing and with the addition of Bionano optical map technology allowed a genome assembly of 451 Mb. The contig sequences obtained by a meta assembly strategy based on CANU 15 and FALCON 16 were scaffolded in a first step using a Bionano optical map and in a second step using a high density genetic map 17 . The chromosome-level assembly (termed Lalb, Table 1, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6d, e, Supplementary Data 15). Instead, we identified a list of candidate genes on Chr18 as associated to the pauper QTL that is responsible for the sweet trait of modern WL accessions, including AMIGA 17,46 (Supplementary Note 9). This region of 958 kb contains 66 genes amongst which several strong candidates encoding for protein with enzymatic activity such as cinnamoyl-CoA reductase and acyltransferases ( Supplementary Data 16).…”
Section: Resultsmentioning
confidence: 99%
“…A Hi-C library was constructed and generated~100-fold coverage of Hi-C linkage data (100 bp paired-end reads). We then linked the contigs into scaffolds based on the Hi-C data 16 with the help of a previously published linkage map 17 ( Supplementary Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Selection for specific adaptation is advisable when targeting severely drought‐prone environments on the one hand and moisture‐favourable environments on the other. Early onset of flowering, which proved controlled by two complementary dominant genes in Adhikari, Buirchell, Yan, and Sweetingham () while showing a polygenic control with respect to vernalization requirement (Książkiewicz et al., ), is a key adaptive trait for drought escape, but variation for intrinsic drought tolerance can be exploited as well within a given phenological class. Selection for wide adaptation is not precluded on the basis of our results and may be justified when targeting less unfavourable or climatically variable regions or, in some cases, because of the limited cultivation and economic importance of the crop.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, this study, whose plant material encompassed much greater diversity of origin than that in earlier studies, indicated the presence of substantial variation in white lupin for drought tolerance and specific adaptation to either drought-stressed or favourable growing conditions. Also, it identified different promising parent material depending on the target environments and the adaptation showing a polygenic control with respect to vernalization requirement (Książkiewicz et al, 2017), is a key adaptive trait for drought escape, but variation for intrinsic drought tolerance can be exploited as well within a given phenological class. Selection for wide adaptation is not precluded on the basis of our results and may be justified when targeting less unfavourable or climatically variable regions or, in some cases, because of the limited cultivation and economic importance of the crop.…”
Section: Discussionmentioning
confidence: 99%